The evangelical alliance mission : an evaluative study of its discipling ministry among the coloured people of Swaziland and South Africa - Matham, Samuel Wilfred (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2002.